IMPORTANT FEATURES OF THE DIPLOMATIC RELATIONS BETWEEN UMAYYAD DYNASTY AND MOVAROUNNAHR (TRANSOXIANA) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article focuses on the content of the initial relations between the Umayyad dynasty and Mоvаrounnahr. Some of them were based on full-fledged diplomatic relations, and some were military in nature. The stable state relations had already been formed here before arriving of the Arabs in this area.